Sub hepatic acute appendicitis: a challenging case to diagnose and successfully managed by laparoscopic procedure - Palle, Pranay; Ramavath, Krishna; Sindhu, Nyna; Parmeshwar, Tushar; Tailor, Sunil B. Boya; Malpuri, Venu B. (International Surgery Journal, 2021)
Sub hepatic acute appendicitis is a rare condition to occur. It can present as right upper quadrant pain and makes challenging in diagnosis and early management. Sub hepatic appendix normally due to malrotation of intestine during developmental period. This condition can mimic as acute cholecystitis, liver abscess. We are presenting a case of sub hepatic acute appendicitis and successfully managed by laparoscopic appendectomy. Sub hepatic acute appendicitis is challenging case to diagnosis and early management. Because late in diagnosis can cause to perforation of appendix and its complications.